Formation of the Mongolian kin of Bordzhigin - Zoriktuev, Bulat R. (The New Research of Tuva, 2014)
Article studies the problem of the formation of the kin of Bordzhigin to which Genghis Khan belonged. The work is based on the studies of the family tree of the Mongolian ruler.
Keywords: family tree of Genghis Khan; Borte-Chino; Bordzhigidai-mergen; Bodonchar